UNIT 15.6 Symmetrical Diamidate Prodrugs of Nucleotide Analogues for Drug Delivery. Issue 1 (9th March 2015) - Pertusati, Fabrizio; McGuigan, Christopher; Serpi, Michaela
Abstract : The use of pronucleotides to circumvent the well‐known drawbacks of nucleotide analogs has played a significant role in the area of antiviral and anticancer drug delivery. Several motifs have been designed to mask the negative charges on the phosphorus moiety of either nucleoside monophosphates or nucleoside phosphonates, in order to increase their hydrophobicity and allow entry of the compound into the cell. Among them the bis‐amidate analogs, having two identical amino acids as masking groups through a P–N bond, represent a more recent approach for the delivery of nucleotide analogs, endowed with antiviral or anticancer activity. Different synthetic strategies are commonly used for preparing phosphorodiamidates of nucleosides. In this protocol, we would like to focus on the description of the synthetic methodology that in our hand gave the best results using 2′‐3′‐didehydro‐2′‐3′‐dideoxythymidine (d4T, Stavudine) as model nucleoside. A second strategy for preparing diamidates of nucleoside phosphonates will be reported using [2‐(6‐amino‐9 H‐purin‐9‐yl)ethoxy]methylphosphonic acid (PMEA, adefovir) as model substrate. © 2015 by John Wiley & Sons, Inc.